Bio-inspired computing – theories and applications : 10th International Conference, BIC-TA 2015 Hefei, China, September 25-28, 2015, Proceedings /: 10th International Conference, BIC-TA 2015 Hefei, China, September 25-28, 2015, Proceedings. (2015) - Unknown
No abstract available